Exploring student creativity in Internet of Things learning through the RADEC model - Felinda Rahma; Syaefudin Saud; Atep Sujana; Leni Permana (AL-TARBIYAH: Jurnal Pendidikan (The Educational Journal), 2026)
Creativity is an essential competency in technology education, particularly in Internet of Things (IoT) learning, which requires students to develop innovative solutions to real-world problems. This study aimed to explore students’ creativity in IoT learning through the implementation of the RADEC (Read, Answer, Discuss, Explain, Create) learning model integrated with differentiated learning at the junior high school level. A descriptive qualitative design with a phenomenological approach was employed. The study involved 28 eighth-grade students and one Informatics teacher at a junior high school in Bandung. Data were collected through classroom observations, semi-structured interviews with the teacher, and documentation of students’ creative products. Data were analyzed using thematic phenomenological analysis. The findings revealed that students demonstrated varying levels of creativity, ranging from Highly Creative to Less Creative categories, based on the indicators of fluency, flexibility, originality, and elaboration. Students generated diverse IoT-based innovation ideas related to communication, healthcare, transportation, environmental sustainability, and daily life. Collaborative discussions and students’ familiarity with digital technology supported creativity development, while low reading interest and teacher readiness remained challenges. The findings suggest that RADEC integrated with differentiated learning provides opportunities for students to express and develop creativity within technology-based learning contexts. Keywords: creativity, Internet of Things, RADEC, differentiated learning, phenomenology